INTEGRATED ENGINEERING/SERVICE TEST OF KIT, CHAPLAIN'S, COMBAT. - Lide, Theodore A.; Lewis, Charleton W.; McGinnis, N. F., Jr.; Leone, Peter N., II.; Sims, Columbus, Jr (1966)
An Integrated Engineering/Service Test of the Chaplain's Kit, Combat, was conducted to determine the technical performance and safety characteristics of the Kit as described in the DA Approved Small Development Requirement (SDR) and as indicated by the particular design, and to determine the suitability of the test item for use by the U.S. Army. The test was conducted by the U. S. Army General Equipment Test Activity (USAGETA); U. S. Army Arctic Test Center (USAATC); and U. S. Army Tropic Test Center (USATTC). It was concluded that the Combat Chaplain's Kit is suitable for use by the U. S. Army in the Arctic, Tropic, and Temperate Zones. The Chaplain's Kit conforms to the SDR with no reported deficiencies but with some shortcomings. It was recommended that the weight limitations in the SDR be waived for the Catholic Chaplain's Kit; the size of the cross be increased; and as many as feasible of the observed shortcomings be rectified.